THE EFFECT OF TEMPERATURE VARIATION ON CONDUCTIVITY VALUE OF CATHODE LITHIUM FERRO PHOSPHATE CARBON COMPOSITE - Mauliana, Metatia Intan; Zainuri, Mochamad (Universitas Negeri Surabaya, 2018)
The lithium ferrous phosphate carbon composite (LFP/C) cathode material has been successfully synthesized using solid-state reaction method by utilizing one of the natural sources of iron rocks in Tanah Laut, Kalimantan, as the base material of Fe. Solid-state reaction method was done by using high energy ball milling tool. The LFP cathode material was prepared using a base material (Li2CO3), Fe3O4, and (NH4)2HPO4 in a ratio of 3:6:2 and 5% wt. of Citric acid as a carbon source. There were some variations of calcination temperature used under inert conditions at 400 °C, 500 °C, 600 °C, and 700 °C to determine the effect on the phase structure and electrical conductivity produced by LFP/C cathode composites. Characterization of phase structure was done by using X-ray powder diffraction (XRD), while the conductivity value of the sample was tested using Electrochemical Impedance Spectroscopy (EIS). The analysis of the diffraction pattern shows the largest composition of olivine structure formed at 700 °C at 93.3% wt. with Fe2O3 impurities of 6.7% wt. The highest conductivity value of LFP/C is shown by sampling with 500 °C calcination temperature with a total conductivity value of 5,676 x 10-3 S.cm-1.